Gene expression and metabolite profiling of thirteen Nigerian cassava landraces to elucidate starch and carotenoid composition - Olayide, P.; Large, A.; Stridh, L.; Rabbi, Ismail Y.; Baldermann, S.; Stavolone, L.; Alexandersson, E. (MDPI, 2020)
The prevalence of vitamin A deficiency in sub-Saharan Africa necessitates effective approaches to improve provitamin A content of major staple crops. Cassava holds much promise for food security in sub-Saharan Africa, but a negative correlation between β-carotene, a provitamin A carotenoid, and dry matter content has been reported, which poses a challenge to cassava biofortification by conventional breeding. To identify suitable material for genetic transformation in tissue culture with the overall aim to increase β-carotene and maintain starch content as well as better understand carotenoid composition, root and leaf tissues from thirteen field-grown cassava landraces were analyzed for agronomic traits, carotenoid, chlorophyll, and starch content. The expression of five genes related to carotenoid biosynthesis were determined in selected landraces. Analysis revealed a weak negative correlation between starch and β-carotene content, whereas there was a strong positive correlation between root yield and many carotenoids including β-carotene. Carotenoid synthesis genes were expressed in both white and yellow cassava roots, but phytoene synthase 2 (PSY2), lycopene-ε-cyclase (LCYε), and β-carotenoid hydroxylase (CHYβ) expression were generally higher in yellow roots. This study identified lines with reasonably high content of starch and β-carotene that could be candidates for biofortification by further breeding or plant biotechnological means.